My Henry - Kerr, Judith (HarperCollins Children's Books, 2012)
Married couples are used to little outings together. Henry's wife can see no reason why they should stop just because one of them has died
Keywords: Bilderbuch; Stories in rhyme; Marriage; Imagination; Death; Premier's Reading Challenge